Household welfare outcomes of access to and use of agricultural radio broadcast by women cocoa farmers in Tepa district, Ghana - Roland Awuah-Frimpong; Enoch Kwame Tham-Agyekum; Fred Ankuyi; Comfort Freeman; Festus Annor-Frempong; John-Eudes Andivi Bakang (Social Sciences and Humanities Open, 2024)
Ghanaian women play a significant part in the country's agricultural marketing, processing and production, yet the gender information gap is severe. This survey aimed to evaluate women's access to and use of agriculture radio broadcasts in the Ashanti Region's Tepa district, Ghana. A descriptive research design and quantitative research method were employed, with a sample size of 300 determined using Cochran's formula. The results indicate that women cocoa farmers have high access to and use cocoa-related information through radio broadcasts. Socio-economic factors such as age, ownership of radio sets, cooperative membership, farm size, and land tenure system significantly affect women's level of access and use of cocoa-related information from radio broadcasts. Women cocoa farmers who utilize the information received from radio broadcasts have improved their household welfare; income, productivity, and livelihood assets. Poor radio signals, lack of finance, and inconvenient broadcast times for women farmers were found to be the most severe constraints. To improve women's household welfare, government agencies should pay more attention to women's information needs.